The prediction of moisture adsorption isotherm for sucrose powder in Côte d’Ivoire - Clément, Yué Bi Yao; Clément, Akmel Djédjro; Kablan, Tano (International Journal of Scientific Research and Management (IJSRM), 2018)
Moisture sorption isotherms play an essential role in preservation and storage of dehydrated food. To study the behavior of sucrose, it’s moisture adsorption isotherm was investigated using the static gravimetrique method at laboratory temperature (29 ±1°C) in a water activity range (aw) of 0.07-0.97. The results showed that the equilibrium moisture content of sucrose increase substantially above aw = 0.6. The moisture adsorption isotherm was sigmoid in shap, showing a type III BET isotherm. The data obtained were fitted to several models including two-parameter (BET, Hasley, Kuhn and Oswin), three parameter (GAB). A non-linear least square regression analysis was used to evaluate the models constants. The GAB model best fitted the experimental data in the wide range of water activity. The best fitted equation provide a sound basis for futur work on the drying and storage of sucrose. The accurate moisture content and the stability profile of sucrose were determined. The results of determination show that sucrose powder was stable below 7.7% RH at 29°C. The content of water adsorbed in the monomolecular layer was calculated (GAB Xm=0.950 g H2O/100 g solids; BET Xm= 1.072 g H2O/100 g solids).